UNISEL ESL Students’ Willingness to Communicate in Second Language - Mohd Yunus, Nur Adlin Hidayah; Pek, Lim Seong; Mee, Rita Wong Mee (Selangor Humaniora Review, 2019)
This present study aims to determine how effective variables and social support affect the learners’ willingness to communicate in L2. The participants are 50 Malaysian students studying in University Selangor majoring in TESL and PAKK. The opinion from both English major students and non-major English students is being collected for this study of their willingness to communicate. This study used questionnaires adapted from a previous study in which 30 questions related to affective variables and social support were distributed to the participants. Most of the participants do not have high motivation to communicate in English because they do not get enough exposure and have low confidence when speaking English. This example indicates that affective variables and social support did affect students’ willingness to communicate.